The Role of Iron in the P-Acquisition Mechanisms of the Unicellular N2-Fixing Cyanobacteria Halothece sp., Found in Association With the Mediterranean Seagrass Posidonia oceanica - Fernández-Juárez, Víctor; Bennasar-Figueras, Antoni; Tovar-Sanchez, Antonio; Agawin, Nona Sheila R. (Frontiers in Microbiology, 2019)
Abstract Posidonia oceanica, an endemic seagrass of the Mediterranean Sea harbours a high diversity of N2-fixing prokaryotes. One of these is Halothece sp., a unicellular N2-fixing cyanobacteria detected through nifH analysis from the epiphytes of P. oceanica. The most related strain in culture is Halothece sp. PCC 7418 and this was used as the test organism in this study. In the Mediterranean Sea, phosphorus (P) and iron (Fe) can be the major limiting nutrients for N2 fixation. However, information about the mechanisms of P-acquisition and the role of metals (i.e. Fe) in these processes for N2-fixing bacteria is scarce. From our genomic analyses of the test organism and other phylogenetically related N2-fixing strains, Halothece sp. PCC 7418 is one of the strains with the greatest number of gene copies (eight copies) of Alkaline Phosphatases (APases). Our structural analysis of PhoD (alkaline phosphatase type D) and PhoU (phosphate acquisition regulator) of Halothece sp. PCC 7418 showed the connection among metals (Ca2+ and Fe3+), and the P-acquisition mechanisms. Here, we measured the rates of Alkaline Phosphatase Activity (APA) through MUF-P hydrolysis under different combinations of concentrations of inorganic P (PO43-) and Fe in experiments under N2-fixing (low NO3- availability) and non-N2 fixing (high NO3- availability) conditions. Our results showed that APA rates were enhanced by the increase in Fe availability under low levels of PO43-, especially under N2-fixing conditions. Moreover, the increased PO43–uptake was reflected in the increased of the P-cellular content of the cells under N2 fixation conditions. We also found a positive significant relationship between cellular P and cellular Fe content of the cells (r2= 0.71, p < 0.05). Our results also indicated that Fe-uptake in Halothece sp. PCC 7418 was P and Fe-dependent. This study gives first insights of P-acquisition mechanisms in the N2-fixing cyanobacteria (Halothece sp.) found in P. oceanica and highlights the role of Fe in these processes.